2023
DOI: 10.1001/jama.2023.19897
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Management in Adults

Arielle Elmaleh-Sachs,
Jessica L. Schwartz,
Carolyn T. Bramante
et al.

Abstract: ImportanceObesity affects approximately 42% of US adults and is associated with increased rates of type 2 diabetes, hypertension, cardiovascular disease, sleep disorders, osteoarthritis, and premature death.ObservationsA body mass index (BMI) of 25 or greater is commonly used to define overweight, and a BMI of 30 or greater to define obesity, with lower thresholds for Asian populations (BMI ≥25-27.5), although use of BMI alone is not recommended to determine individual risk. Individuals with obesity have highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(36 citation statements)
references
References 132 publications
0
21
0
Order By: Relevance
“…While MOVE! and similar lifestyle counseling interventions are evidence-based avenues to weight loss, medications and surgery produce substantially more weight loss on average (12,37). Thus, this set of results indicating lower access to more intensive, more effective treatments among minoritized patients is troubling, even if access to MOVE!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While MOVE! and similar lifestyle counseling interventions are evidence-based avenues to weight loss, medications and surgery produce substantially more weight loss on average (12,37). Thus, this set of results indicating lower access to more intensive, more effective treatments among minoritized patients is troubling, even if access to MOVE!…”
Section: Discussionmentioning
confidence: 99%
“…Incretin-based injectable medications join the existing arsenal of evidence-based, guidelinerecommended obesity treatments, including behavioral weight loss programs, older anti-obesity medications, and bariatric surgery (8)(9)(10)(11)(12), all of which were underutilized in the era prior to incretinbased therapy (13)(14)(15)(16)(17)(18)(19). As marginalized populations frequently receive healthcare innovations slower and later than more resource-rich counterparts (20,21)-and given inequities in use of existing obesity treatments (18,19,(22)(23)(24)(25)-it is far from certain that these next-generation medications are diffusing equitably.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in this putative overlap has been heightened by recent reports that GLP-1 receptor agonists (GLP-1RAs)—approved for treating type 2 diabetes and obesity—may represent potential new pharmacotherapies for AUD (Leggio et al, 2023). Similarly, medications used to treat AUD reduce weight in individuals with obesity (Elmaleh-Sachs et al, 2023). For example, topiramate, recommended as an off-label treatment for AUD (Perry et al, 2022; Reus et al, 2018), is approved in combination with phentermine as a weight loss medication.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, medications used to treat AUD reduce weight in individuals with obesity (Elmaleh-Sachs et al, 2023). For example, topiramate, recommended as an off-label treatment for AUD (Perry et al, 2022;Reus et al, 2018), is approved in combination with phentermine as a weight loss medication.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 However, available dietary weight‐loss programs, including commercialized diets, very‐low‐calorie diets, and academia‐developed programs, are insufficient in the magnitude of weight loss and sustainability of lost weight. 6 , 7 , 8 , 9 To the best knowledge of the Individualized Diet Improvement Program (iDip) group, only one study demonstrated the major reversal of type 2 diabetes lasting for 2 years using a ketogenic diet. 10 , 11 Outcomes of behavioral weight loss are similar to dietary weight loss in magnitude and sustainability.…”
Section: Introductionmentioning
confidence: 99%